Flow-Dependent Concentration Polarization and the Endothelial Glycocalyx Layer: Multi-Scale Aspects of Arterial Mass Transport and their Implications for Atherosclerosis - Vincent,PE; Weinberg,PD (Biomech Model Mechanobiol, 2013)
Atherosclerosis is the underlying cause of most heart attacks and strokes. It is thereby the leading cause of death in the Western world, and it places a significant financial burden on health care systems. There is evidence that complex, multi-scale arterial mass transport processes play a key role in the development of atherosclerosis. Such processes can be controlled both by blood flow patterns and by properties of the arterial wall. This short review focuses on one vascular-scale, flow-regulated arterial mass transport process, namely concentration polarization of low density lipoprotein at the luminal surface of the arterial endothelium, and on one cellular-scale, structural determinant of arterial wall mass transport, namely the endothelial glycocalyx layer. Both have attracted significant attention in recent years. In addition to reviewing and appraising relevant literature, we propose various directions for future work.